Synonymy in the armoured scale insect genus Unaspis MacGillivray (Hemiptera: Coccomorpha: Diaspididae) - Watson, Gillian W. (Zootaxa, 2015)
In recent years, an undescribed species of Unaspis MacGillivray (Hemiptera: Coccomorpha: Diaspididae) has become a damaging pest on the fruit crop Lansium domesticum Corrêa (family Meliaceae) in the Philippines.